The process of formation of mental health for nurses in primary health care - Neves, Hilton Giovani; Lucchese, Roselma; Munari, Denize Bouttelet; Vera, Ivania; Santana, Fabiana Ribeiro (Rev Rene, 2012)
This study was based on descriptive, exploratory and qualitative approach and aimed at analyzing scientific knowledge that was developed in the formation of Family Health (FH) nurses to address Mental Health in Primary Care regarding psychosocial aspects. Research conducted in 2008 with three teams of FH nurses a municipality in the countryside of Mato Grosso, whose data were submitted to content analysis. The results were organized according to two themes "The limitations of official spaces for the training of nurses" and "The Family Health as well as the transformation praxis in Mental Health ". It was concluded that the official spaces mentioned above do not give too much importance to education on mental health, the same occurs in the context of lifelong learning. Despite the limited provision of skills for Mental Health care, we have found significant changes such as the sensitization to emotional and psychological manifestations of the population with higher awareness of health.